Functional Imaging of Liver Cancer (FLIC): Study protocol of a phase 2 trial of 18F-DCFPyL PET/CT imaging for patients with hepatocellular carcinoma. - Esther Mena; Joanna Shih; Joon-Yong Chung; Jennifer Jones; Atoosa Rabiee; Cecilia Monge; Baris Turkbey; Liza Lindenberg; Kilian E Salerno; Michael Kassin; Brad Wood; Jonathan Hernandez; et al. (PLoS ONE)
Background While prostate specific membrane antigen (PSMA) is overexpressed in high-grade prostate cancers, it is also expressed in tumor neovasculature and other malignancies, including hepatocellular carcinoma (HCC). Importantly, no functional imaging for HCC is clinically available, making diagnosis and surveillance following local therapies particularly challenging. 18F-DCFPyL binds with high affinity to PSMA yet clears rapidly from the blood pool. PET imaging with 18F-DCFPyL may represent a new tool for staging, surveillance and assessment of treatment response in HCC. The purpose of this Functional Imaging Liver Cancer (FLIC) trial is to assess the ability of 18F-DCFPyL-PET/CT to detect sites of HCC. Methods This is a phase II multi-site prospective imaging trial with a plan to enroll 50 subjects with suspected HCC on standard of care CT or MRI and eligible for standard local treatment. Participants will undergo a baseline 18F-DCFPyL-PET/CT, prior to therapy. Subjects will also be scanned with 18F-FDG-PET/CT within 2 weeks of 18F-DCFPyL-PET/CT. Participants will undergo histopathologic assessment and standard of care local treatment for HCC within a multidisciplinary team context. Participants with histopathologic confirmation of HCC and a positive baseline 18F-DCFPyL-PET/CT will undergo a post-treatment 18F-DCFPyL-PET/CT during the first routine follow-up, typically within 4-8 weeks. Subjects with negative baseline 18F-DCFPyL-PET/CT will not be re-scanned after treatment but will remain in follow-up. Participants will be followed for 5-years to assess for progression-free-survival. The primary endpoint is the positive predictive value of 18F-DCFPyL-PET for HCC as confirmed by histopathology. Secondary endpoints include comparison of 18F-DCFPyL-PET/CT with CT, MRI, and 18F-FDG-PET/CT, and evaluation of the value of 18F-DCFPyL-PET/CT in assessing treatment response following local treatment. Exploratory endpoints include next generation sequencing of tumors, and analysis of extracellular vesicles to identify biomarkers associated with response to therapy. Discussion This is a prospective imaging trial designed to evaluate whether PSMA-PET/CT imaging with 18F-DCFPyL can detect tumor sites, assess local treatment response in HCC patients, and to eventually determine whether PSMA-PET/CT could improve outcomes of patients with HCC receiving standard of care local therapy. Importantly, this trial may help determine whether PSMA-selective radiopharmaceutical therapies may be beneficial for patients with HCC. Clinical trial registration NIH IND#133631. Submission date: 04-07-2021. Safe-to-proceed letter issued by FDA: 05.07.2021. NIH IRB #00080. ClinicalTrials.gov Identifier NCT05009979. Date of Registry: 08-18-2021. Protocol version date: 01-07-2022.